URGENSI MEMBANGUN LITERASI PADA ANAK USIA DINI - Munawarah Munawarah; Chairun Nisa Fadhilah; Reza Aulia; Nur Cahyati Ngaisah; Firman Priyo Suhasto (Jurnal Dedikasi Pendidikan, 2023)
Literacy is an ability that must exist from an early age. Literacy in early childhood is synonymous with the child's ability to recognize and understand. Literacy also plays an important role in a child's life, besides being useful for being able to communicate children are also expected to be able to solve problems. The method of this research is to use the study library research method which aims to examine more deeply related to early childhood literacy. In obtaining this research data obtained from journals and related articles that can support the answers to the problem formulation in this study. Data analysis techniques were carried out in three stages, namely collecting, processing and concluding. The results of the study show that building literacy in children can be done by reading fairy tales to children, inviting children to read in the park as a form of providing opportunities for children to learn in a new atmosphere, providing a reading platform namely "Cakruk Read Moves", then using the He's Handsome method. namely by the method of communication with fellow friends